Designing Note Sharing Application on Android Platform - Jenie, Renan Prasta; Hutomo, Karyana; Wijaya, Freddy (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Writing notes on paper is fun because we can simply write whatever we want on it. Writing notes in the digital media is also advantageous for it can be shared directly. If we can combine the two functions, it will be more profitable. Therefore, the author wants to combine the benefits of writing as you wish like as on paper with contemporary digital writing. Somehow, writing using PC cannot be done at any time due to the needs of both electrical connection and space availabilty. Therefore, Smartphone or tablet is the right choice because it is not tied to two needs. The Smartphone to be selected is the one built with android platform for ease of note transfer compared to other platforms.